Monthly progress report of July 2021 of BRAC University new campus development project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding monthly progress report of July 2021 of BRAC University new campus development project.